Dispersion Parameters and Electrical Characterization of Cd₁₋ₓCuₓS Thin Films Deposited by Using AACVD Technique - Mohammed Jasim, Zaid; B. Hasan, Nahida; K. Al-khaykanee, Mohsin (Al-Nahrain Journal of Science, 2026)
In this research, an aerosol-assisted chemical vapor deposition (AACVD) was successfully employed to synthesize Cd₁₋ₓCuₓS (0 ≤ x ≤ 1) semiconductor thin films. The structural, morphological, and optical properties of the deposited films were systematically investigated as a function of copper concentration using energy-dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), and UV-Vis spectroscopy. The results demonstrated that the optical behavior of the films is strongly influenced by Cu incorporation. Specifically, an increase in CdS fraction resulted in a decrease in the Urbach energy, whereas the activation energy exhibited a progressive increase with higher CuS content.